Meningkatkan daya ledak otot tungkai menggunakan media elastic band pada pemain futsal - Inzaghi, Rizki Ahmad; Syaukani, Agam Akhmad (Jurnal Porkes, 2023)
This study aims to determine the effect of the elastic band training model on increasing the explosive power of the limb muscles of futsal players. The problem of this research is the lack of golden tringle physical factors for athletes or futsal players. The results of testing the hypothesis are accepted, namely that there is an effect of the elastic band training model on increasing the explosive power of the leg muscles. This research is a quantitative type with experimental methods. The design used is a quasi-experimental design using one-group pretest-posttest. The number of subjects in this study was 15. The researchers provided an exercise program with 14 treatments using elastic bands and 2 standing broad jump test meetings. The data analysis technique used to test the hypothesis is the t-test. Based on the research results, the tcount value is -15.900 with a significance value of 0.000. The result of calculating the sig value obtained is 0.000 which is smaller than 0.05. It is concluded that Ha is accepted and Ho is rejected. So the conclusion of this study is that training using elastic bands to increase the explosive power of the leg muscles is evidenced by the posttest average value of 2.34m better than the pretest of 1.96m, an increase of 0.38m.